ETHNOLINGUISTIC STUDY OF AGRICULTURAL VOCABULARY AT KASEPUHAN CIPTAGELAR SUKABUMI - Laksmana Putra, Dodik Murdiyanto; Rais, Wakit Abdullah; Sawardi, Sawardi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
Rice culture society, which is a society that has a set of supernatural values and beliefs in rice entities. As a strong rice-cultured society, all main activities of Kasepuhan Ciptagelar community are centered on rice. There are many series of rituals performed during one cycle of rice planting. This study attempts to describe the problem (1) how the forms of Sundanese vocabulary are used in a series of rituals of rice culture during one cycle of rice planting in Kasepuhan Ciptagelar Sukabumi , (2) how the lexical meaning and cultural meaning of those terms, (3) how the functions of the meaning. This research is a qualitative descriptive study with an ethnolinguistic approach. This descriptive qualitative research also utilizes ethnographic methods. Ethnographic methods are used in this study because data collection is done directly. The analysis model used is a model of cognitive anthropology or ethnoscience or also known as the new ethnography. The location of this research is in the Kasepuhan Ciptagelar Indigenous community in the area of Mount Halimun Salak National Park, Sukamulya Village, Sirnaresmi Village, Cisolok District, Sukabumi Regency, West Java. Based on data analysis in this study, there were 32 series of rituals from cultural activities carried out for 10 months in one cycle of rice planting in Kasepuhan Ciptagelar.